Understanding Gender Justice: Asma Barlas Perspective on Women and the Qur’an - Fitryansyah, Muhammad Andryan (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2024)
This research explores Asma Barlas perspective on gender justice in Islam, particularly in the context of Qur’anic interpretation. Barlas, through her work “Believing Women in Islam: Unreading Patriarchal Interpretations of the Qur’an,” offers a critical hermeneutic approach to traditional interpretations that tend to be patriarchal. A descriptive-analytical qualitative approach was used to analyze Barlas works and compare them with other interpretations. Data were collected through literature review and document analysis. Thematic analysis identifies and understands the main themes in Barlas interpretations, including the principles of gender justice she proposes. The results show that Barlas rejects the patriarchal view often found in traditional commentaries and asserts that the Qur’an, when read with a just and non-patriarchal approach, supports gender equality. The research also discusses the fundamental differences between Barlas' interpretation and traditional exegesis, as well as the potential impact of her thinking on the contemporary Islamic feminist movement. Challenges and criticisms of Barlas approach are analyzed to provide a balanced view of the strengths and limitations of her methodology. This research highlights the importance of an inclusive hermeneutic approach in Qur’anic exegesis and offers a new perspective for developing a more just understanding of gender in Islam.